THE IMPACT OF NON-PERFORMING LOANS ON COMPANY PROFITS - Laynita Sari; Febryandhie Ananda; Dewi Zulfia; Muhammad Rivandi; Mike Kusuma Dewi (Nindikayla Institute, 2023)
This study aims to determine the effect of Non-Performing Loans on the profits of banking companies in Indonesia. Non-performing loans and company profit are obtained from the company's financial statements and from the Indonesia Stock Exchange website. The research sample amounted to four banks of State-Owned Enterprises in Indonesia from 2014-2022. The type of data used is secondary data in the form of annual reports of State-Owned Enterprises Banks for the 2014-2022 period. The data analysis technique uses multiple linear regression analysis with the help of the E-Views program version 12.Â This study found that Non-Performing Loans provide empirical evidence of a significant negative effect on the profits of banking companies of State-Owned Enterprises Banks in 2014-2022 significantly